2021
DOI: 10.5644/ama2006-124.313
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use Among Croatian Health Studies Students– A Single Center Cross-Sectional Study

Abstract: <p><strong>Objective. </strong>The use of complementary and alternative medicine (CAM) among healthy population and in patients with certain health conditions has been investigated in Croatia; however, no studies have been carried out among health studies students and professionals. The aim of the study was to measure the extent of CAM use among health studies students.</p><p><strong>Materials and Methods. </strong>An online survey was used to question students enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several studies have been conducted to assess the perceptions and knowledge of different population groups regarding herbs [ 18 , 19 ]. However, few articles have been conducted in the dental field [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to assess the perceptions and knowledge of different population groups regarding herbs [ 18 , 19 ]. However, few articles have been conducted in the dental field [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with growing data on conventional oncology therapeutic modalities, consulting patients and family members about CAM utilization for most healthcare professionals still presents quite a challenge [8]. The incidence of CAM consumption in Croatia varies from 15% in the general population to 54.6% among healthy university students [9][10]. While the prevalence of CAM use among Croatian adult oncology patients was reported as 35%, no studies on pediatric cancer patients in Croatia have been conducted so far [11].…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, a significant increase in CAM use in developed and developing countries was noticed. 8,9 It has been reported that more than half of the world's population are CAM users. 9 CAM has been used to manage many diseases, including mild conditions (e.g., common cold, diarrhea, and headache) and chronic diseases (e.g., diabetes, chronic kidney impairment, and high blood pressure).…”
Section: Introductionmentioning
confidence: 99%